The Influence Of Product Quality, Brand Image, And Service Quality On The Purchasing Decision Of Mixue Teluk Gong Ice Cream - Aldi Setiawan; Tri Waluyo; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to determine the effect of product quality, brand image, and service quality on purchasing decisions at Mixue Ice Cream and at Tea Teluk Gong. The sample data collection method used is Non-Probability Sampling with Purposive Sampling technique. This type of research uses descriptive quantitative methods and inferential analysis using primary data in the form of questionnaires to 100 respondents and data analysis using multiple linear regression analysis. Based on the data that has fulfilled the validity test, reliability test, classic assumption test and model feasibility test, the regression equation is obtained. The results of the regression analysis in this study show that there is a positive and significant influence on consumer purchasing decisions, which are displayed in the Coefficient table in the form of a regression equation. The results of the model feasibility test are displayed as a significant value displayed in the model feasibility table, which means that the model in this study is feasible to use based on the significant value obtained. The results of the conclusion of the hypothesis with the t test based on the significant value of the variables Product quality, brand image and service quality on consumer purchasing decisions.